Supportive comment on: “Morphology and population of binary asteroid impact craters”, by K. Miljkovic, G.S. Collins, S. Mannick and P.A. Bland [Earth Planet. Sci. Lett. 363 (2013) 121–132] – An updated assessment - Schmieder, Martin; Trieloff, M.; Schwarz, W.H.; Schwarz, W.; Buchner, E.; Jourdan, Fred (Elsevier Science BV, 2014)
In their recent paper, Miljkovic et al.(2013) assess the apparent contradiction that the near-Earth asteroid population consists of 15% binaries, while the terrestrial (and Martian) impact crater populations have only 2–4% of observable doublet craters. The authors suggest that only a small fraction of sufficiently well separated binary asteroids yield recognizable doublets. We generally agree with the conclusions by Miljkovic et al. (2013) and acknowledge the high quality and relevance of the study. However, we would like to bring into focus additional geochronologic constraints that are critical when evaluating terrestrial impact crater doublets. Miljkovic et al. (2013) appraised five potential terrestrial doublets using the Earth Impact Database (EID; as of 2010). We hereby warn against the indiscriminate usage of impact ages compiled in this database without an assessment based on solid isotopic and stratigraphic constraints and comment on the geological, geochronological, and geochemical evidence for doublet impact craters on Earth.